The Effects of Tourism Web Development on Prospective Travelers by Considering Persuasive and Liking Principles - Wasino; Dyah Erny Herwindiati; Haris Maupa (International Journal of Social Science and Business, 2022)
The essential foundation for Indonesia's tourism is the use of information technology effectively. One of the ways is building a tourism website with a well-maintained response and Persuasive message. The construction of a tourism website must be measured in quality based on what users feel about the website. This study aims to build a tourism website that can affect user perception and is preferred by users. In addition, the intention is to create a positive mental image of content about tourist destinations that are preached through the tourism website. In this study build a responsive tourism website using general methods or techniques such as fluid grid layouts and media queries-screen resolution. Data collection from participants as respondents through this questionnaire uses a rating scale. Then for analyses is used persuasive index and liking index assessment criteria. Persuasive and Liking methods or principles in constructing this tourism website are well implemented. This research produced a tourism website tested in a white box and a black box. The Black box testing such as alpha testing, is conducted by internal users, and external users conduct beta testing. This tourism website has been implemented. The test results show that the effect level is large and the user's favorite level is high level. The persuasive principle with the liking principle has a strong relationship or correla.